Positive relationship of higher daily pedometer activity with active sexual behaviour and semen quality parameters of young Sahiwal bulls (Indian Journal of Animal Production and Management, 2024)
The present investigation was conducted on newly developed pedometer under NAIP Project in collaboration  with IIT Delhi, to correlate find association of activity of Sahiwal bulls (SW) with sexual behaviour and semen  production performance at Artificial Breeding Research Centre, ICAR-National Dairy Research Institute,  Karnal, Haryana, India. The average pedometer activity of seven bulls was 5421.34±1049.67 and the bulls  were divided into two groups, i.e. Group 1 (Four bulls showed lower pedometer activity than average) and  Group 2 (three bulls showed higher pedometer activity than average). The data were analyzed by T-test  using SAS 9.3. It is evident from the results that pedometer activity (3361.06±482.69 vs.8168.39±802.36),  penile protrusion score (1.34±0.08 vs. 1.74±0.08), ejaculatory thrust score (1.48±0.16 vs. 2.38±0.15), mating  ability score (70.78±3.23% vs. 83.08±4.58%), ejaculate volume (2.65±0.22ml vs. 4.37±0.26ml), mass  activity on scale 1-5 (2.61±0.14 vs. 3.52±0.09), initial progressive motility (65.92±2.79%vs.80.00±1.23%)  and sperm concentration (966.50±55.37 million/ml vs. 1352.82±45.59 million/ml) differ significantly (p
Keywords: Pedometer activity; Sexual behavior; Semen quality; Sahiwal bulls